2008
DOI: 10.1161/circulationaha.107.722249
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Preventability of Death After Coronary Artery Bypass Graft Surgery and All-Cause Risk-Adjusted Mortality Rates

Abstract: Background-The goal of this study was to determine the relationship between all-cause, risk-adjusted, in-hospital mortality after coronary artery bypass graft surgery and the proportion of preventable in-hospital deaths as a measure of quality of care at an institution level. Methods and Results-We conducted a retrospective analysis of 347 randomly selected in-hospital deaths after isolated coronary artery bypass graft surgery at 9 institutions in Ontario over the period of 1998 to 2003. Nurse-abstracted chart… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
45
0
2

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 69 publications
(49 citation statements)
references
References 40 publications
(30 reference statements)
2
45
0
2
Order By: Relevance
“…A recent study in Ontario examined deaths among patients who underwent bypass surgery at various institutions. 9 Although the Ontario hospitals had favorable mortality rates, about a third of the deaths were deemed preventable had optimal care been provided. That analysis indicated opportunities for improvement in the care of these patients.…”
Section: What Should Clinicians Do?mentioning
confidence: 99%
“…A recent study in Ontario examined deaths among patients who underwent bypass surgery at various institutions. 9 Although the Ontario hospitals had favorable mortality rates, about a third of the deaths were deemed preventable had optimal care been provided. That analysis indicated opportunities for improvement in the care of these patients.…”
Section: What Should Clinicians Do?mentioning
confidence: 99%
“…We are striving toward this goal by working with our stakeholders to develop and collect consensus quality measures with a rigorous independent data audit (25). In addition, rather than simply measuring outcome rates, our region will have provided more detailed independent feedback on how adverse outcomes relate to quality of care problems (26). We anticipate that providing clinically relevant feedback will provide a clearer roadmap to direct quality improvement activities.…”
Section: Misinterpretation By Public Press and Governmentmentioning
confidence: 99%
“…However, process change represents the major aspect of health care delivery under providers' control. If hospital standardized mortality ratios correlate poorly with the need for process changes (as in the study by Dubois and colleagues and a recent study from Ontario 3 ), it remains unclear how hospital standardized mortality ratios can serve as a useful screen for quality problems.…”
Section: [The Authors Respond:]mentioning
confidence: 99%
“…Mooney and colleagues found that studies of nicotine replacement therapies are generally not blind in that participants correctly guess assignment at rates significantly above chance. 2 When this finding is combined with the meta-analytic finding by Eisenberg and colleagues that smoking cessation with pharmacologic treatment is nearly always more successful than cessation without pharmacologic treatment in clinical trials and the fact that cessation with pharmacological treatment has failed to be more successful than cessation without such treatment in nearly all of real-world surveys conducted to date, 3 it strongly suggests that the pharmacologic treatment of chemical dependency may be the only known research area in which blinding is impossible.…”
Section: Smoking Cessation Trialsmentioning
confidence: 99%